Single-leg landing coordination variability and second injury in young athletes after primary anterior cruciate ligament reconstruction - Perry, J. A.; Kronenberg, J. M.; Thomas, S. M.; Paterno, M. V.; Siston, R. A.; Schmitt, L. C. (Medicine & Science in Sports & Exercise, 2026)
Purpose: Young, active individuals who undergo anterior cruciate ligament (ACL) reconstruction (ACLR) after an ACL injury often experience suboptimal outcomes, including a high risk of second ACL injury. Coupling angle variability has been used previously to investigate the interactions between joints and their relative coordination, but it has not yet been used to investigate the future risk of subsequent ACL injury during dynamic tasks post-ACLR. As such, the purpose of this work was to examine the relationship between coordination variability and second ACL injury outcomes in young athletes after primary ACLR, along with uninjured controls.